The use of Guthrie’s theory in a combination of stimulus and response - Sianipar, Yules Orlando (NOTION: Journal of Linguistics, Literature, and Culture, 2024)
Eliminating punishment can lead to a lack of focus or the emergence of bad habits that can affect the teaching and learning process. Stimulus and response should be given continuously as Guthrie suggested. The Contiguous Conditioning Theory created by Edwin Ray Guthrie (1886-1959) says the punishment given during the learning process is needed to change a person's behavior, exercises and tests or tests need to be done to get used to the stimulus that is needed. The purpose of this research are 1) to find the effects of using punishment, reward, exercise, and test (fatigue method), 2) to find The Contiguous Conditioning Theory using fatigue method in one single trial learning can be a new technique in learning English. It is experimental research. The result shows the Guthrie theory of fatigue method in one single trial learning is considered appropriate. The use of punishment and rewards gives a better stimulus. The experiment group has a better average point.